PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PKn DENGAN MODEL PBL DI SD - Nelsi, Yulia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Based on preliminary studies and observations of student researchers and fifth grade teacher at SDN 05 V Koto Timur district. V Koto Timur Kab. Padang Pariaman, student learning outcomes is still low and the learning undertaken by teachers are still using conventional methods. So the author through this research trying to improve student learning outcomes in subjects Civics. The purpose of this study was to describe the planning, implementation and learning outcomes. This research is action research (class action research), this study used a qualitative approach. Learning is used by using the method of problem based learning. After doing research hence an increase in student learning outcomes in Civics lesson using problem based learning. It can be seen, both from the ability of teachers in designing learning from 76.50% up to 88.50%, 77.50% of all teachers increased to 87.50%, from 75.00% student activity increased to 85.00%. From the students' mastery increased 68.39% to 82.32%. Kata Kunci: hasil belajar; pendidikan kewarganegaraan; model pbl